When the results overlap the indicator: : analysis of the Rede Cuidar Program - Soares, Helena Teixeira Magalhães; Morais, Reinaldo Carvalho de; Assis, Marcos Arcanjo de (Revista Aval, 2025)
The article addresses the relationship between indicators and social policies with the following question: is it possible to evaluate social policies based on the reference indicator for proposing action? The hypothesis is that factors intrinsic and external to the process can reconfigure actions and results not appropriate by the indicator. The object of study was the Rede Cuidar Program, which is a social assistance policy that uses the Indicator of Reception Units of the Unified Social Assistance System (ID Acolhimento). In the descriptive analysis, parameterization was carried out between the composition of the indicator and the status of institutions, references to interviews and statistical analysis using Pearson's Chi-square test, which showed the absence of association between the types of investments with the indicator, except with the action plan. It is concluded that the evaluation of social policies requires the expansion of parameters to extrapolate indicators.